Pelestarian Tari Zapin Istana Siak oleh Sanggar Balairung Sri Kecamatan Siak Kabupaten Siak Provinsi Riau - Febriana Fernandes; Idawati Idawati (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
This research aims to determine the preservation of the Zapin Istana Dance by the Balairung Sri Studio, Siak District, Siak Regency, Riau Province. Preservation is how to maintain, preserve and develop all existing culture or traditions. The theory that researchers use is the conservation theory by Edy Sedyawati. The method used in this research is descriptive analysis, with a qualitative approach. The findings from this research are that the Zapin Istana Dance is still maintained and preserved today by some people in Siak Regency, especially the Balairung Sri Studio. Conservation is carried out in accordance with Edy Sedyawati's theory which consists of three aspects, namely protection, development and utilization.